2013
DOI: 10.1007/s40264-013-0113-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measures in Safety Event Reporting: PROSPER Consortium Guidance

Abstract: The Patient-Reported Outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 44 publications
(49 reference statements)
1
78
0
Order By: Relevance
“…As the experience in using these measures increased it became obvious that there is a clinical value in using individual patient PROs profiles in daily practice to give clinicians standardized information on patient problems to identify/monitor symptoms, evaluate treatment outcomes and support shared decisionmaking. [2][3][4][5][6][7][8] Recently, PROs became widely accessible to clinicians via electronic/online reporting with new developments towards integration with Electronic Health Records (EHRs) via patient portals. 2 The integration of PROs with clinical data in EHRs offers innovative opportunities of including patient perspective in Big Dataset for analysis and rapid learning from combined biological, clinical and treatment information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the experience in using these measures increased it became obvious that there is a clinical value in using individual patient PROs profiles in daily practice to give clinicians standardized information on patient problems to identify/monitor symptoms, evaluate treatment outcomes and support shared decisionmaking. [2][3][4][5][6][7][8] Recently, PROs became widely accessible to clinicians via electronic/online reporting with new developments towards integration with Electronic Health Records (EHRs) via patient portals. 2 The integration of PROs with clinical data in EHRs offers innovative opportunities of including patient perspective in Big Dataset for analysis and rapid learning from combined biological, clinical and treatment information.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of PROs is increasingly recognized as an essential part of drug safety reporting, Comparative Effectiveness Research and patient-centred outcomes approaches. [3][4][5][6] However, these innovative opportunities can only be realized if practicing clinicians understand the values of PROs in patient care and start collecting and utilizing the information in their daily work. The barriers to implementing the use of PROs in routine clinical care 7 included scepticism about the validity of patient self-report, unfamiliarity with PROs, preference for physiologic measures, and uncertainty how to interpret the information and make it actionable in clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…The fragmented nature of PV in the global context presents the UMC with a multitude of challenges. Currently, problems such as under-reporting and the communication of incomplete, unrepresentative, and uncontrolled data prove to be significant barriers to detecting and characterising new adverse drug interactions and ADRs [7]. A 2016 study by Bailey et al [8] identified 108 ADR reporting systems and highlighted a number of challenges associated with the lack of a standardised ADR reporting form.…”
Section: Contextmentioning
confidence: 99%
“…The important role of patients in identifying, describing, and ultimately avoiding, harm from medicines is increasingly recognized [1,2], and modern technologies are being explored to facilitate patient engagement [3]. Information on direct patient reports in pharmacovigilance differs in certain respects from information provided by health professionals, but has been found to be of complementary value [4].…”
mentioning
confidence: 99%
“…The former resemble the free-text narratives of individual case reports, should be encoded in standard E2B format 2 , and captured by the regular pharmacovigilance system, presuming that they fulfil reporting requirements. This will enable their inclusion in regular pharmacovigilance signal detection and analysis.…”
mentioning
confidence: 99%